What is the value of ( 4 0 2 + 3 8 2 + … + 4 2 + 2 2 ) − ( 3 9 2 + 3 7 2 + … + 3 2 + 1 2 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I just used a computer but this solution is much more elegant.
Nicely done.
thanxx
How did you reach this expression: (40)(41)/2 ?
Log in to reply
Using gauss therom, you add up 40+39+38+...+3+2+1, which will give you (40+1)*(40-0)/2
The expression was taken from the formula for the sum of the first n integers of a sequence (n(n+1))/2
u can also use Sn = n/2(2a + (n-1)d) n=nos.of series a=first nos d=diff. if u use this expression for 1+2+3+4....n u will get n(n+1)/2
nice im not sapereating so i not do nice
nice!!!!!!very good explanation i wish like you. hehehhe galng brad!!! :)
n(n+1)/2 use only arithmetic progression
I made C code to solve it :P , but n!ce solution
If we look at the differences on a pairwise basis, we can can rewrite the problem as ∑ n = 1 2 0 ( 2 n ) 2 − ( 2 n − 1 ) 2 or as the recurrence: f ( 0 ) f ( n ) = 0 = f ( n − 1 ) + ( 2 n ) 2 − ( 2 n − 1 ) 2 , 1 ≤ n ≤ 2 0 Expanding the first term in the pairwise difference simplifies the recurrence relation: f ( n ) = f ( n − 1 ) + ( 2 n ) 2 − ( 2 n − 1 ) 2 = f ( n − 1 ) + 4 n 2 − 4 n 2 + 4 n − 1 = f ( n − 1 ) + 4 n − 1 When a recurrence relation is of the form f ( n − 1 ) + g ( n ) where g ( n ) is a polynomial in n , we can write a generic function of one degree higher than g to find a closed form solution to f : f ( n ) = A n 2 + B n + C Since we have 3 unknowns, we need 3 equations. Choosing n = 1 , 2 , 3 , we have: A + B + C 4 A + 2 B + C 9 A + 3 B + C = 3 = 1 0 = 2 1 Solving this system reveals A = 2 , B = 1 and C = 0 , which gives the closed form solution: f ( n ) = 2 n 2 + n Evaluating for n = 2 0 we find that f ( 2 0 ) = 2 × 4 0 0 + 2 0 = 8 2 0 .
Nice writeup on how to deal with a more general problem!
Wait I didn't know we could use math
Sum of squares of first n natural numbers = [ n (n+1) (2n+1) ] / 6
Sum of squares of first n odd natural numbers = [ n (2n-1) (2n+1) ] / 3
(refer Proof at http://www.9math.com/book/sum-squares-first-n-odd-natural-numbers)
The expression in the question equals to
( Sum of squares of first 40 natural numbers - Sum of squares of first 20 odd natural numbers) - Sum of squares of first 20 odd natural numbers
= Sum of squares of first 40 natural numbers - 2 x Sum of squares of first 20 odd natural numbers
= [ 40 (40+1) (2x40+1) ] / 6 - 2 [ 20 (2x20-1) (2x20+1) ] / 3
= 820
Most people know the sum of squares of first n positive integers. Do you also know the sum of squares of first n odd positive integers?
How can you derive it?
I also used the same idea to solve it(but i did it without reading your solution!!!).
( 4 0 2 − 3 9 2 ) + ( 3 8 2 − 3 7 2 ) + . . . + ( 2 2 − 1 2 )
= ( 4 0 + 3 9 ) + ( 3 8 + 3 7 ) + . . . + ( 2 + 1 )
= 3 + 7 + . . . + 7 9
= 2 2 0 × ( 3 + 7 9 ) ; [ 3 + ( n − 1 ) 4 = 7 9 ⇔ n = 2 0 ]
= 8 2 0
(2..40).step(2).to a.collect{|i| i*i}.inject(:+)-(1..39).step(2).to a.collect{|i| i*i}.inject(:+)
Let's rewrite...
( 4 0 2 + 3 8 2 + . . . + 4 2 + 2 2 ) − ( 3 9 2 + 3 7 2 + . . . + 3 2 + 1 2 )
= ( 4 0 2 − 3 9 2 ) + ( 3 8 2 − 3 7 2 ) + . . . + ( 4 2 − 3 2 ) + ( 2 2 − 1 2 )
= ( 4 0 + 3 9 ) ( 4 0 − 3 9 ) + ( 3 8 + 3 7 ) ( 3 8 − 3 7 ) + . . . + ( 4 + 3 ) ( 4 − 3 ) + ( 2 + 1 ) ( 2 − 1 )
= ( 4 0 + 3 9 ) + ( 3 8 + 3 7 ) + . . . ( 4 + 3 ) + ( 2 + 1 )
= 4 0 + 3 9 + 3 8 + 3 7 + . . . + 4 + 3 + 2 + 1
Now it's just a simple arithmetic progression... It's the sum of first 40 positive integers...
We know the formula for finding out the sum of first n positive integers...
That is, 2 n ( n + 1 )
Simple plugging in n = 4 0 , we get...
2 4 0 × ( 4 0 + 1 ) = 2 4 0 × 4 1 = 2 0 × 4 1 = 8 2 0
Hence, the required answer is 8 2 0
Find the difference of 40 squared and then 39 squared and do the same for 38 squared and 37 squared. Compare both and u will realise as the number go down they reduce by 4. So take 79 and keep minus with 4 till you reach 3 because the last one is 2 squared minus 1 squared which is 3.
The question can be broken into two series:
First series is the sum of squares of first 20 even natural numbers: ( 4 0 2 + 3 8 2 + . . . + 4 2 + 2 2 )
Second series is the sum of squares of first 20 odd natural numbers: ( 3 9 2 + 3 7 2 + . . . + 3 2 + 1 2 )
The answer is the difference between these two sums.
Therefore,
( 4 0 2 + 3 8 2 + . . . + 4 2 + 2 2 ) = 3 2 n ( n + 1 ) ( 2 n + 1 ) = 3 2 . 2 0 . ( 2 0 + 1 ) ( 2 . 2 0 + 1 ) = 1 1 4 8 0
and
( 3 9 2 + 3 7 2 + . . . + 3 2 + 1 2 ) = 3 n ( 2 n − 1 ) ( 2 n + 1 ) = 3 2 0 . ( 2 . 2 0 − 1 ) ( 2 . 2 0 + 1 ) = 1 0 6 6 0
Hence, the final solution,
( 4 0 2 + 3 8 2 + . . . + 4 2 + 2 2 ) − ( 3 9 2 + 3 7 2 + . . . + 3 2 + 1 2 ) = 1 1 4 8 0 − 1 0 6 6 0 = 8 2 0 which is the required answer.
( 4 0 2 - 3 9 2 )+( 3 8 2 - 3 7 2 )+...+( 2 2 - 1 2 )=(40+39)(40-39)+(38+37)(38-37)+...(2+1)(2-1)=40+39+38+37+...+2+1=820
40^2-39^2 +38^2-37^2............. 2^2-1^2 (40+39)(40-39)+(38+37)(38-37)..............................(2+1)(2-1) Taking one common , we get 1* (1+2+3+4+5........................40) 1*(40(40+1)/2 = 820
You could've used formatting to make your solution more readable.
I know that this isn't the correct way, but I used the following python code:
list_1=[x**2 for x in range(2,41,2)]
list_2=[x**2 for x in range(1,40,2)]
print sum(list_1)-sum(list_2)
On opening the brackets and rearranging the given sequence it follows -
(40^2 - 39^2) + (38^2 - 37^2) + (36^2 - 35^2) + ......... +(2^2 - 1^2) this implies, (40+39)(40-39) + (38+37)(38-37) + ........... +(2+1)(2-1) this implies, (40+39)(1) + (38+37)(1) + ....... +(2+1)(1) this implies, 40+39+38+37+.......+2+1
(40^2-39^2)+(38^2-37^2)+...+(2^2-1^2)=
(40+39)(40-39)+(38+37)(38-37)+...+(2+1)(2-1)=
79+75+...+3=
(20/2)(79+3)=(10)(82)=820
I think in last step u used AP.
(40^2 + 38^2 +…+ 4^2 + 2^2) − (39^2 + 37^2+…+3^2 + 1^2) = (40^2 - 39^2) + (38^2 - 37^2) +...+(4^2 - 3^2) + (2^2 - 1^2) = 79 + 75 + 71 + 67 + ....+ 11 + 7 + 3 = 20/2 (79 + 3) = 10 x 82 = 820
Problem Loading...
Note Loading...
Set Loading...
We can group the given expression into:
( 4 0 2 − 3 9 2 ) + ( 3 8 2 − 3 7 2 ) + . . . + ( 2 2 − 1 2 ) , and with the use of the identity a 2 − b 2 = ( a + b ) ( a − b )
= ( 4 0 2 − 3 9 2 ) + ( 3 8 2 − 3 7 2 ) + . . . + ( 2 2 − 1 2 ) = ( 4 0 + 3 9 ) ( 4 0 − 3 9 ) + ( 3 8 + 3 7 ) ( 3 8 − 3 7 ) + . . . + ( 2 + 1 ) ( 2 − 1 ) = ( 4 0 + 3 9 ) ( 1 ) + ( 3 8 + 3 7 ) ( 1 ) + . . . + ( 2 + 1 ) ( 1 ) = ( 4 0 + 3 9 + 3 8 + 3 7 + . . . + 2 + 1 ) = ( 4 0 ) ( 4 1 ) / 2 = 8 2 0
Answer: 8 2 0